Holistic characterization analysis of tar waste content from gasification process at Surakarta landfill - Rahayu, Putu Elsa Purnama; Rachmawati, Siti; Setyono, Prabang (Intelektual Pustaka Media Utama, 2024)
Surakarta is facing serious problems related to waste management at the Putri Cempo landfill. PT. Solo Citra Metro Plasma Power with the Surakarta city government built a waste power plant installation with gasification technology. Tar waste is a gasification liquid product that is dangerous if not managed. This study aimed to determine the heavy metal content and toxicity level of gasified tar waste using the atomic absorption spectrometry (AAS) and lethal dose-50 (LD50) acute toxicity test. The parameters of heavy metals tested are lead (Pb), copper (Cu), iron (Fe), zinc (Zn), and total chromium (Cr). In the LD50 test, the animals were divided into 5 groups, namely 1 control group and 4 groups with doses of 0.50 mL, 1 mL, 2 mL, and 4 mL. The results showed that the tar contained 17.4 mg/L of iron, 3.5 mg/L of zinc, and <0.01 mg/L of lead, copper, and chromium. Acute toxicity tests did not cause death in the animals but still showed toxic symptoms, so the LD50 value is declared pseudo. The content of some heavy metals in tar is within safe limits and the level of toxicity is relatively harmless.